2022 World of Shipping Portugal: An international research conference on maritime affairs - Ana Cristina Paix\~ao Casaca; Maria Amélia Ramos Loja (Journal of Shipping and Trade (JST), 2023)
The COVID-19 pandemic has changed the world. It showed the possibility of running economic activities remotely, allowing people to learn how to have a more balanced life. As a result, electronic commerce flourished, and it is here to stay. However, only time will tell whether people will shop more online or return to traditional brick-and-mortar shopping. With more people at home, prevented from going out to a cinema, or a theatre, the service industry was severely impacted until governments relieved the confinement measures so that their economies returned to pre-pandemic levels. Certainly that container shipping was the winner of all shipping market segments, given the increased number of finished goods to be carried. When all seemed to return to normalcy, the Russian-Ukraine crisis complicated the economic and political environment. Maritime transport was affected in the Black Sea, and only after many weeks of negotiation did the parties involved reach the Ukraine grain deal enabling Ukraine to transport millions of tonnes of food through the Black Sea despite the ongoing conflict. The number of sanctions against Russia increased, and many countries and regions were forced to look for alternative sources of oil, oil by-products and gas, this time benefiting the gas and tanker shipping markets with increasing freight rates. Apart from this, the maritime industry is still facing extraordinary challenges. Endeavours are being made to accelerate industry decarbonisation, digitalisation and operations optimisation. The quest for finding alternative fuels to power the world fleet is there. For now, LNG and methanol are the most promising alternatives, with the possible installation of carbon storage units to mitigate carbon dioxide emissions into the atmosphere. These events draw the industry to deal with the market, technology, and regulatory challenges and risks whose outcome is yet to be seen. With this background, seven papers presented at the 2022 World of Shipping Portugal Conference, An International Research Conference on Maritime Affairs, 27-28 January, that took place online via CiscoWebex due to the Covid-19 pandemic were selected to be published in this Special Issue. They open the scope for new research areas and address essential aspects that contribute to the efficiency of the overall maritime sector.
Keywords: 650; Cold ironing; Container shipping; Digitalisation; Maritime accidents; Maritime security; Maritime transport; Port community systems; Port governance